Characterization of seed longevity traits by using molecular markers in soybean [Glycine max (L.) Merrill] - BHARAMARAJ BADIGER; RAVI HUNJE; N. K. BIRADAR PATIL; D. P. BIRADAR; VILAS A. TONAPI (Seed Research, 2026)
Soybean [Glycine max (L.) Merrill] genotype varies in storability period during ambient storage. In this study, six genotypes of soybean, varying in storability, were characterized with 14 SSR markers. Out of 14 primers screened for seed longevity, the primer Satt 285, Satt 316, Satt 434 and Satt 538 gave distinct banding pattern. They produced an amplicon size range of 184 bp for those genotypes which are having poor seed longevity amongst the studied genotypes and the same loci produced amplicon size range up to 235 bp for those genotypes having good seed longevity.